Testing the relationship between tourism receipts , economic growth and the real effective exchange rate in Algeria during the period (1995 - 2020) using cointegration and Toda yamamoto causality - KARA Brahim,; CHEKALIL Imane,; RATOUL Mohamed, (Journal of North African Economies, 2025)
This study aims to testing and analyzing the relationship between tourism receipts , economic growth and real effective exchange rate in Algeria over the period (1995 -2020), using cointegration and toda yamamoto causality test the johansen cointegration test show that a long run relationship exists between variables, The impact of tourism receipts on economic growth is about 1.571074 % this effect is statistically significant at 5% level also a significant causal relationship in the short run is found from LTRSM and LREER to LGDP at 1% and 5 % level of significant according to toda yamamoto causality test